Isocrates II - Gagarin, Michael,Mirhady, David,Papillon, Terry L.,Too, Yun Lee (University of Texas Press, 2004)
This is the seventh volume in the Oratory of Classical Greece. This series presents all of the surviving speeches from the late fifth and fourth centuries BC in new translations prepared by classical scholars who are at the forefront of the discipline. These translations are especially designed for the needs and interests of today's undergraduates, Greekless scholars in other disciplines, and the general public. Classical oratory is an invaluable resource for the study of ancient Greek life and culture. The speeches offer evidence on Greek moral views, social and economic conditions, political and social ideology, law and legal procedure, and other aspects of Athenian culture that have been largely ignored: women and family life, slavery, and religion, to name just a few. The Athenian rhetorician Isocrates (436-338) was one of the leading intellectual figures of the fourth century. This volume contains his orations 4, 5, 6, 8, 12, and 14, as well as all of his letters. These are Isocrates' political works. Three of the discourses-Panathenaicus, On the Peace, and the most famous, Panegyricus-focus on Athens, Isocrates' home. Archidamus is written in the voice of the Spartan prince to his assembly, and Plataicus is in the voice of a citizen of Plataea asking Athens for aid, while in To Philip, Isocrates himself calls on Philip of Macedon to lead a unified Greece against Persia.
10.7560/702455
Keywords: Speeches; addresses; etc; LITERARY CRITICISM / Ancient & Classical